Differential activity of a lectin from Solieria filiformis against human pathogenic bacteria - M.L. Holanda (Brazilian Journal of Medical and Biological Research, 2005)
A lectin isolated from the red alga Solieria filiformis was evaluated for its effect on the growth of 8 gram-negative and 3 gram-positive bacteria cultivated in liquid medium (three independent experiments/bacterium). The lectin (500 µg/mL) stimulated the growth of the gram-positive species Bacillus cereus and inhibited the growth of the gram-negative species Serratia marcescens, Salmonella typhi, Klebsiella pneumoniae, Enterobacter aerogenes, Proteus sp, and Pseudomonas aeruginosa at 1000 µg/mL but the lectin (10-1000 µg/mL) had no effect on the growth of the gram-positive bacteria Staphylococcus aureus and B. subtilis, or on the gram-negative bacteria Escherichia coli and Salmonella typhimurium. The purified lectin significantly reduced the cell density of gram-negative bacteria, although no changes in growth phases (log, exponential and of decline) were observed. It is possible that the interaction of S. filiformis lectin with the cell surface receptors of gram-negative bacteria promotes alterations in the flow of nutrients, which would explain the bacteriostatic effect. Growth stimulation of the gram-positive bacterium B. cereus was more marked in the presence of the lectin at a concentration of 1000 µg/mL. The stimulation of the growth of B. cereus was not observed when the lectin was previously incubated with mannan (125 µg/mL), its hapten. Thus, we suggest the involvement of the binding site of the lectin in this effect. The present study reports the first data on the inhibition and stimulation of pathogenic bacterial cells by marine alga lectins.